2019
DOI: 10.21608/scumj.2019.44181
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Immunosuppressive Drug Sirolimus on structure of the Submandibular Salivary Glands of the Rat

Abstract: Background: Submandibular salivary glands are responsible for secretion of major amount of saliva which is important for normal oral environment of the oral cavity. Aim: to evaluate the effect of the Immunosuppressive drug Sirolimus on structure and immunohistochemistry of the submandibular salivary glands of the rats. Material and Methods Forty healthy adult male albino rats (body weight 150 -180 gram) were divided into two equal groups 20 animals each. Group 1 served as controls while group 2 were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
(12 reference statements)
2
2
0
Order By: Relevance
“…Our results are in agreement with the findings of Soliman et al [ 18 ]. The authors revealed that the administration of rapamycin was associated with morphological changes in the rat submandibular salivary gland.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results are in agreement with the findings of Soliman et al [ 18 ]. The authors revealed that the administration of rapamycin was associated with morphological changes in the rat submandibular salivary gland.…”
Section: Discussionsupporting
confidence: 94%
“…Other authors [ 16 , 18 ] have described more intense morphological changes in the salivary glands of animals after immunosuppressive treatment compared to our observations. These changes might result from the use of daily doses of immunosuppressive drugs that were higher than those applied in our experiment.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations